Jaminan Kredit Pada Perjanjian Kredit Sindikasi - Susilowati Susilowati (Pusat Riset dan Inovasi Nasional, 2022)
Credit Guarantee in the Syndicated Bank Credit Agreement is the most important guarantee in the Syndicated Credit Agreement which is the main discussion in this Legal Writing. The method that the author uses in this legal research is normative juridical, where the documents used as guidelines in the preparation are primary legal documents and secondary legal documents. The Credit Guarantee in the Syndicated Credit Agreement that I will use is a credit guarantee with concession rights which includes toll road concession revenues, escrow accounts, and insurance claims. The Credit Guarantee is important to cover or guarantee the Creditors in the Syndicated Bank in the event of a default or bad credit or default from the Debtor. Collateral as regulated in Law number 7 of 1992 concerning Banking as amended by Law number 10 of 1998 concerning Amendments to Law number 7 of 1992 concerning Banking, guarantee is defined as